The risk factors of the occurrence of inguinal hernia in ESRD patients receiving dialysis treatment: An observational study using national health insurance research database. Issue 49 (9th December 2022) - Chiu, Pin-Han; Liu, Jui-Ming; Hsieh, Ming-Li; Kao, Wei-Tang; Yu, Kai-Jie; Pang, See-Tong; Lin, Po-Hung
Abstract : With the quickly growing population of patients receiving dialysis treatment in Taiwan in recent years, concerns about whether more incidence of inguinal hernia exists in dialysis patients are increasing. In Taiwan, peritoneal dialysis (PD) and hemodialysis (HD) are the 2 most common dialysis types. Therefore, the relationship between dialysis type and inguinal hernia occurrence needs to be evaluated and compared. Our retrospective cohort study included a study population total of 3891 patients diagnosed with end stage renal disease (ESRD) under the HD or PD procedure from 2001 to 2009 from the Longitudinal Health Insurance Database. Also, International Statistical Classification of Diseases and Related Health Problems 9th Revision codes were used to identify ESRD and hernia occurrence. Cox proportional-hazards regression model was applied to measure the risk factors to the hernia occurrence. During the follow-up periods of 3 years, the number of hernia occurrences was 44 (1.13%), 1 (0.03%), and 8 (0.21%) with inguinal, femoral, and ventral hernias, respectively. Only the dialysis type revealed significantly increased hernia risk because PD would increase hernia risk 7 times (adjusted hazard ratio [aHR] = 6.98, 95% CI = 3.59–13.25) than HD. If the patients received PD and shifted to HD later, the risk of hernia was 5 times (aHR = 4.98, 95% CI = 2.29–10.85) than patients with HD. Patients with ESRD receiving PD or PD-HD shift were risk factors of inguinal hernia occurrence. The results may help clinicians increase the alert of possible risk factors and complications at the beginning of dialysis treatment in patients with ESRD.